Comparative Analysis of Economic and Social Results of Foreign and Domestic Firms: Case Russian Electronic Industry; International Business Information Management Association Conference, IBIMA - Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Shabaldina N. V. Nataliya Vladimirovna; Novoseltseva D. A. Darjya Andreevna (2015, 2015)
Title screen